Barriers and facilitators to health information exchange in low- and middleincome country settings: a systematic review protocol. Issue 2 (1st April 2015) - Akhlaq, Ather; Sheikh, Aziz; Pagliari, Claudia
Abstract : Introduction: The ability to capture, exchange and use accurate information about patients and services is vital for building strong health systems, providing comprehensive and integrated patient care, managing public health risks and informing policies for public health and health financing. However, the organisational and technological systems necessary to achieve effective health information exchange are lacking in many low- and middle-income countries (LMIC). Developing strategies for addressing this depends on understanding the barriers and facilitators to health information exchange (HIE) at the individual, provider organisational, community, district, provincial and national levels. This systematic review aims to identify, critically appraise and synthesise the existing published evidence addressing these factors. Objective: To assess what is known, from published/unpublished empirical studies, about barriers and facilitators to HIE in LMIC so as to identify issues that need to be addressed and approaches that can fruitfully be pursued in future improvement strategies. Methods: We will conduct a systematic review to identify the empirical evidence base on the barriers and facilitators to HIE in LMIC. Two reviewers will independently search 11 major international and national databases for published, unpublished and in-progress qualitative, quantitative and mixed methods studies published during 1990–July 2014 in any language. These searches of scientific databases will be supplemented by the eligible reports available online. The included studies will be independently critically appraised using the Mixed Method Appraisal Tool, version 2011. A descriptive, narrative and interpretative synthesis of data will be undertaken. Results: These will be presented in an article that will be published in the peerreviewed literature. The protocol is registered with the International Prospective Register for Systematic Reviews (PROSPERO) CRD 42014009826.